Register and register labeling in dictionaries. - Crenn, Tiphaine. (University of Ottawa (Canada), 1996)
Dictionaries employ usage labels to warn the user of restrictions on the use of a word. Register labels are just one of several types of usage labels. Differentiating between various usages has been a practice since the very beginnings of monolingual French and English lexicography in the seventeenth century. However, the advent of sociolinguistics in the latter half of this century, and the concept of language varieties, which has emerged from sociolinguistic studies, has had an impact on lexicography. In theory, dictionaries now generally recognize that register, or use-related varieties of language (i.e. tied to the situation in which the speaker uses language), is not a question of right and wrong, only one of appropriateness. In practice, however, there are discrepancies from dictionary to dictionary in the treatment of register and register labeling. An in-depth look at the front matter or a few dictionaries, monolingual and bilingual, reveals both the lack of a clear notion of register in lexicography and inadequate explanation of the basis on which words are labeled for register. An extensive examination of the actual entries found within these dictionaries, however, reveals a certain common thread in register labeling since some labels can be found in all dictionaries, and certain words are always labeled. Although some consistency in register labeling does exist, marking words for register is always problematic since it is subjective. An examination of a few entries prepared at the Bilingual Canadian Dictionary project shows the difficulty of labeling register consistently even when specific guidelines are proposed to lexicographers. The usefulness of consulting on-line corpora as a more objective basis for labeling is examined, and certain recommendations are made to improve the consistency of register labeling in bilingual lexicography in general, and especially in the Bilingual Canadian Dictionary. (Abstract shortened by UMI.)
Keywords: Language, Linguistics.